Advanced operating systems and kernel applications techniques and technologies - Wiseman, Yair; Jiang, Song (Information Science Reference, 2010)
As any application running on a computer makes use of the operating system, the potential impact of improving areas such as memory management, process scheduling, file systems, and device drivers is tremendous. Advanced Operating Systems and Kernel Applications: Techniques and Technologies discusses non-distributed operating systems that benefit researchers, academicians, and practitioners desiring to delve into this subject area and learn more on this important field of study. This publication includes an overview of topical issues, methods, and advancements in the field of one-processor operating systems
Includes bibliographical references and index
Keywords: Operating systems (Computers); Betriebssystem; Kernel -- Informatik; Aufsatzsammlung